Implementasi Metode Diskusi dalam Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran Fiqih - Wilda, Diah Awwanda; Nursyamsiyah, Siti; Huda, Hairul (Jurnal Pendidikan Islam, 2024)
The discussion method is highly essential to be implemented in education with the aim of increasing students' motivation, leading them towards independence and responsibility. So far, fiqh learning has been carried out in a monotonous manner, involving memorization of theories, which has resulted in student boredom during the learning process. Therefore, the Madrasah Aliyah has transformed this method by incorporating the discussion method to address cognitive, affective, and psychomotor aspects. This research employs a qualitative approach, collecting data through observation, interviews, and documentation. The data analysis technique is inductive analysis, and data validity is ensured through source triangulation. Findings from this research indicate that the discussion method is capable of transforming students' knowledge from passive to active, thus improving fiqh learning outcomes. Additionally, the discussion model influences student motivation in enjoyable learning, making the material easier to remember and applicable in daily life.